2008
DOI: 10.1007/s10519-008-9214-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Phenotypes Associated with Mood and Anxiety Among Male and Female Fragile X Premutation Carriers

Abstract: The fragile X disorder spectrum, due to a CGG expansion in FMR1, includes fragile X syndrome (>200 repeats) and the premutation-associated disorders of ovarian insufficiency and tremor/ataxia syndrome (approximately 55-199 repeats). Altered neurobehavioral profiles including variation of phenotypes associated with mood and anxiety may be expected among younger premutation carriers given this spectrum of disorders. However, previous studies have produced conflicting findings, providing the motivation to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 39 publications
5
53
1
Order By: Relevance
“…4852 Recent studies found a relationship between the number of CGG repeats and the prevalence 50 and severity 51 of depressive symptoms. The prevalence of major depressive disorder is high for women with a PM relative to the national average, with a higher than expected rate of first major depressive disorder episodes occurring before the birth of a child with FXS.…”
Section: Resultsmentioning
confidence: 99%
“…4852 Recent studies found a relationship between the number of CGG repeats and the prevalence 50 and severity 51 of depressive symptoms. The prevalence of major depressive disorder is high for women with a PM relative to the national average, with a higher than expected rate of first major depressive disorder episodes occurring before the birth of a child with FXS.…”
Section: Resultsmentioning
confidence: 99%
“…In fXPCs, there is higher prevalence of ADHD diagnoses in women (Hunter, Rohr, & Sherman, 2010) and boys (Farzin et al, 2006) and increased ADHD symptoms in men (Dorn, Mazzocco, & Hagerman, 1994) and boys (Aziz et al, 2003). Furthermore, self-reported inattention and impulsivity in female fXPCs is positively associated with CGG repeat length (Hunter et al, 2008a). Indicative of impaired cognitive inhibition, fXPCs report higher levels of obsessive-compulsive symptoms, which are positively associated with mRNA levels (Hessl et al, 2005)).…”
Section: Executive Function In Fxpcs Asymptomatic For Fxtasmentioning
confidence: 99%
“…A recent large family survey of children with the full mutation and premutation, in which parents were simply asked whether their child had been diagnosed with or been treated for a range of conditions, showed that 33.3% of 57 males and 35.6% of 119 females with the premutation were identified as having significant anxiety, compared to 8.8% of males and 15.3% of females with normal FMR1 alleles matched for age and family income (28). However, it should be noted that Hunter and colleagues (29) examined mood and anxiety in 119 males and 446 females age 18-50 ascertained from families with a history of FXS and from the general population. Repeat length was not associated with anxiety, but was marginally associated with depression and negative affect in males and negative affect only in females.…”
Section: Introductionmentioning
confidence: 99%